Child Neurology: Maternal Transmission of Congenital Myotonic Dystrophy Type 2: Case Report. (13th December 2022) - Tieleman, Alide A.; Damen, Manon J.; Verrips, Aad; Roelofs, Monique; Kamsteeg, Erik-Jan; Voermans, Nicol C.
Abstract : Congenital manifestations in Myotonic Dystrophy type 2 (DM2) point to anticipation and have only rarely been described. We report a three-generation family with genetically confirmed DM2. The youngest family member presented with unilateral congenital pes planovalgus and equinus. Genetic analysis in four family members showed a CCTG repeat expansion in the CNBP gene. We highlight the association between foot deformities and congenital DM2. Remarkably, the transmission to the congenital form of DM2 has been exclusively maternal so far. If this association is confirmed in other families, clinical practice and genetic counseling in DM2 families need to be adapted.